Importance-performance analysis in the hospitality business: the example of a three star hotel - Dimitrieva, Rita (2020)
Such spheres of business activity as tourism and hospitality as well as related contextual environments entail the provision of some kind of service. In recent years, the service industry has grown in importance, with hotel business being one of the main components. However, it is common knowledge that the principal factor of prosperity and success in the hotel industry is aiming attention at people: both employees and guests. Currently, one of the key tasks of managing the organization involved in the service sector is to meet the needs of customers by creating a proper within-a-hotel environment, in which employees become loyal to the company and oriented towards achieving organizational goals. Having as an example of a three-star hotel in a Spanish competitive touristic city, which rooms can be reserved in a well know and very dissected web platform was made a survey to its guests to understand their perception regarding the attributes they consider more important in a hotel when they choose one and the real performance of the hotel, regarding the same attributes, after their stay. The results were compared and analysed using an importance-performance analysis, which has several benefits for the assessment of the guests’ satisfaction. It is a budget-oriented, simple and comprehensible technique that allows having an insight into the attributes that should be prioritized. The results of the survey show the performance of the hotel matches the importance given by the guests to the attributes and matches the satisfaction the guest publish in the social networks.